A Visual Mapping: Uncovering the Silencing and Secrecy of Abuse in the Lives of South African Indian Women’s Love Narratives - Madhi, Saajidah (University of the Witwatersrand, Johannesburg, 2024)
Using Autoethnography as a research approach, this dissertation explores how storytelling and poetry can be used to unveil South African Indian women’s lived experiences of Indian culture and generational teachings. This is explored in conjunction with how love and secrecy/silencing (which is the aftermath of abuse) co-exist in heterosexual relationships. In this context, unveiling refers to the uncovering of women’s narratives, the stories that have been silenced, erased, or overlooked, due to women often being judged and shamed for expressing their suffering. Throughout this dissertation, my poetry is utilized to address these issues. Furthermore, this dissertation analyses South African Indian women’s narratives using qualitative research (interviews) that questions the notions of how love, patriarchy, Indian cultural beliefs, and identity influence relationships. To achieve this, Chapter One outlines the key concepts of love, patriarchy, Indian identity, and generational beliefs, through literature that is interwoven with South African Indian women’s experiences. This is followed by Chapter Two, which engages in gendered roles, silencing, secrecy, and the impact that media has on romance and love in relationships. Lastly, Chapter Three proposes the model of unlearning as a practice. In this context, unlearning refers to a transformation of learned knowledge to build safer and non-violent relationships. To critically examine the practice of veiling in South African Indian women's lives, my artwork actively explores various methods of veiling. These methods include covering, layering, uncovering, and recovering, and they act as tools to voice a subjective position on women’s silencing through weaving, stitching, and beading.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; South African Indian women; Lenasia; domestic violence; poetry; visual artwork and visual mappin; SDG-5: Gender equality